2016
DOI: 10.1038/labinvest.2016.51
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-1 regulates osteoblast and lipoblast precursor cells in mice

Abstract: Imbalances in lipid metabolism affect bone homeostasis, altering bone mass and quality. A link between bone mass and high-density lipoprotein (HDL) has been proposed. Indeed, it has been recently shown that absence of the HDL receptor scavenger receptor class B type I (SR-B1) causes dense bone mediated by increased adrenocorticotropic hormone (ACTH). In the present study we aimed at further expanding the current knowledge as regards the fascinating bone-HDL connection studying bone turnover in apoA-1-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 38 publications
10
64
0
Order By: Relevance
“…Frozen samples of lumbar vertebrae were cryosectioned, exploiting the CryoJane® Tape‐Transfer system and tungsten blades (Leica Biosystems, Wetzlar, Germany). Mineralized surface and interlabel distance were evaluated by measuring calcein labels in the cancellous bone using the grid intersect method, and interlabel distance using minimum pixel interval at high power, as reported . Bone formation parameters were expressed as bone formation rate (BFR) and mineral surface over bone surface (MS/BS).…”
Section: Methodsmentioning
confidence: 99%
“…Frozen samples of lumbar vertebrae were cryosectioned, exploiting the CryoJane® Tape‐Transfer system and tungsten blades (Leica Biosystems, Wetzlar, Germany). Mineralized surface and interlabel distance were evaluated by measuring calcein labels in the cancellous bone using the grid intersect method, and interlabel distance using minimum pixel interval at high power, as reported . Bone formation parameters were expressed as bone formation rate (BFR) and mineral surface over bone surface (MS/BS).…”
Section: Methodsmentioning
confidence: 99%
“…2001). We have very recently reported that APOA1 deficiency greatly disturbs the ANXA2-CLCX12-CXCR4 connection, providing a plausible mechanistic explanation for the impaired osteoblastic function observed in the ApoA1 KO mice (Blair et al 2016). It should also be borne in mind that the CLCX12-CXCR4 axis is also crucial for the regulation of osteoblastic bone marrow niche that participates in an array of processes, including hematopoietic stem cell (HSC) homing and mobilization and bone metastasis (Greenbaum et al 2013, Kfury & Scadden 2015).…”
Section: The Effect Of the Components Of The Hdl Metabolic Pathways Omentioning
confidence: 97%
“…Through a series of in vitro and molecular experiments on mesenchymal stem cells, osteoblasts and osteoclasts isolated and cultured from femora of the two mouse groups we uncovered that the osteoblast-related factors and signaling axes, RUNX2, osterix, COLLa1, RANKL, were significantly impaired in the ApoA1 KO as compared to the wild type mice. On the contrary, genes that regulate osteoclastic differentiation and function namely TRAP ( Acp5 ), cathepsin K ( Ctsk ) and RANK ( Tnfrsf11a ), were unaffected (Blair et al 2016). These interesting findings indicate that the reduced bone mass observed in the ApoA1 KO mice, is attributed primarily to suppressed osteoblastic bone synthesis and not to increased osteoclastic bone degradation.…”
Section: The Effect Of the Components Of The Hdl Metabolic Pathways Omentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vivo, fatty acids are a key source for bone synthesis 12 ; elimination of the major HDL component causes severe osteoporosis. 13 Osteoblasts that are not synthesizing bone are low-columnar cells, but still form a continuous membrane (Fig. 1A).…”
Section: Fundamental Bone Organization and Cell Biologymentioning
confidence: 99%